Measuring the Comparability of Company Accounts Conditionally: A Research Note - Taplin, Ross (Wiley Blackwell, 2017)
© 2017 Accounting Foundation, The University of Sydney Comparability indices summarize the level of comparability between companies at a national and international level, an issue of importance to investors, regulators, and standard setters. Comparability indices can identify areas where comparability is low and where comparability is deteriorating. Furthermore, they can be used to quantify the extent to which initiatives such as International Financial Reporting Standards (IFRS) are successful in raising comparability between company accounts. Despite past literature emphasizing how factors other than country influence accounting methods used by companies, current comparability indices ignore these other factors. This paper introduces new national and international indices within the T index framework to fill this gap in the literature. Formula for the new national and international indices, and their standard errors, are provided. An example using European data is used to demonstrate the calculations and illustrate the importance of controlling for these firm specific factors.